The energy internet : an open energy platform to transform legacy power systems into open innovation and global economic engines - Su, Wencong; Huang, Alex Q. (Woodhead Publishing in energy., 2019)
The Energy Internet: An Open Energy Platform to Transform Legacy Power Systems into Open Innovation and Global Economic Engines is an innovative concept that changes the way people generate, distribute and consume electrical energy. With the potential to transform the infrastructure of the electric grid, the book challenges existing power systems, presenting innovative and pioneering theories and technologies that will challenge existing norms on generation and consumption. Researchers, academics, engineers, consultants and policymakers will gain a thorough understanding of the Energy Internet that includes a thorough dissemination of case studies from the USA, China, Japan, Germany and the U.K. The book's editors provide analysis of various enabling technologies and technical solutions, such as control theory, communication, and the social and economic aspects that are central to obtaining a clear appreciation of the potential of this complex infrastructure.